2021
DOI: 10.1145/3463408
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of the COVID-19 pandemic on computing students' sense of belonging

Abstract: Sense of belonging, or belongingness, describes how accepted one feels in their academic community and is an important factor in creating inclusive learning environments. Belongingness is influenced by many factors including: students' backgrounds and experiences; other people; environments (physical and virtual); academic discipline; external factors such as local, regional, and global issues; and time. 2020 has been dominated by several major events including the COVID-19 pandemic which dramatically impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 36 publications
0
12
0
1
Order By: Relevance
“…The IMV model argued that there were three steps in the emergence of suicidal ideation: defeat – entrapment – suicidal ideation. The COVID‐19 pandemic caused considerable social isolation (Hamza et al, 2021), interpersonal rejection (Mooney & Becker, 2021), challenges in online learning (Adnan, 2020), hopelessness (Tao, Niu, Hou, et al, 2023), the loss of future development opportunities (Lee et al, 2021), financial failure (Nicola et al, 2020), and concerns about personal health and safety (Soria & Horgos, 2021), which are all the roots of feelings of defeat (Turecki & Brent, 2016; Williams et al, 2017). An Indian study (Sripad et al, 2021) found that several early cases of suicide resulting from the impact of COVID‐19 pandemic in India were directly attributed to the stigma and social ostracism associated with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The IMV model argued that there were three steps in the emergence of suicidal ideation: defeat – entrapment – suicidal ideation. The COVID‐19 pandemic caused considerable social isolation (Hamza et al, 2021), interpersonal rejection (Mooney & Becker, 2021), challenges in online learning (Adnan, 2020), hopelessness (Tao, Niu, Hou, et al, 2023), the loss of future development opportunities (Lee et al, 2021), financial failure (Nicola et al, 2020), and concerns about personal health and safety (Soria & Horgos, 2021), which are all the roots of feelings of defeat (Turecki & Brent, 2016; Williams et al, 2017). An Indian study (Sripad et al, 2021) found that several early cases of suicide resulting from the impact of COVID‐19 pandemic in India were directly attributed to the stigma and social ostracism associated with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…It could be that those struggling with depression, anxiety, eating disorders, or financial insecurity were unwilling to participate in the study. It is important to point out here that recent studies have shown that mental health varies greatly from person to person during the pandemic ( Kelly et al, 2021 ; Mooney and Becker, 2021 , 2021h lund, 2021 ) and that eating disorders have generally increased ( Zhang, 2021 ). Although we do not assume that for most of them, as most of them declined us politely with sound reasons (such as a lack of time, since the interviews had to be carried out within a narrow time span).…”
Section: Limitations and Future Workmentioning
confidence: 95%
“…Mooney and Becker [46] investigated the impact of the pandemic on computing students' sense of belonging as discussed in section 8. Their study was motivated by a university-wide survey of the students at their university in 2020 where half of students ranked "COVID-related stress and anxiety" as "extremely challenging" or "very challenging".…”
Section: Health and Wellness 61 Prior Workmentioning
confidence: 99%
“…Mooney and Becker [46] surveyed undergraduate computing students over a three-year period between 2017 and 2020, asking about their sense of belonging. The researchers found that "COVID-19 had a larger impact on the sense of belonging of all students in the space of a few months than we otherwise observed over the two prior years".…”
Section: Community Building 81 Prior Workmentioning
confidence: 99%